Changing bodies: Experiences of women who have undergone a surgically-induced menopause - Pearce, G.; Thøgersen-Ntoumani, Cecilie; Duda, J.; McKenna, J. (Sage Publications, 2014)
We aimed to explore the lived experiences of women who had a surgical menopause as a result of undergoing a hysterectomy with Bilateral Salpingo-Oopherectomy (BSO). We adopted a qualitative interview design using Interpretative Phenomenological Analysis (IPA), and recruited 7 women aged 47 to 59. We conducted synchronous online semistructured interviews using the MSN (Microsoft Network) Messenger program. In the findings, we examine the prominent and underresearched theme of body image change. We discuss the women’s journey from a deep internal bodily change, the meaning of this changing body image, through to the thoughts and behaviors involved with self-presentation concerns and coping with body image changes. A woman’s perceived attractiveness and appearance investment are important factors to consider regarding adaptation to change over this transition. The findings might have implications for interventions designed to enhance mental well-being and increase health behaviors in women experiencing gynecological illness and/or menopause.